Microstructure and Mechanical Properties of Copper, Nickel and Ternary Alloys Cu-Ni-Zr Obtained by Mechanical Alloying and Hot Pressing - Ordonez, S (Materials Research Society, 2017)
Elemental powders of Cu and Ni, binary alloys (Cu-Ni and Cu-Zr) and ternary alloy (Cu-Ni-Zr) obtained by mechanical alloying and uniaxial compaction hot microstructure and mechanical properties were investigated. The alloys studied were: pure Cu, pure Ni, binary alloys (Cu-Ni; Cu-Zr) and ternary alloys (Cu-Ni-Zr) under the same mechanical milling and hot pressing conditions. The samples were analyzed by X-ray diffraction (XRD), scanning electron microscope (SEM); the mechanical properties were studied by compression tests and hardness in Vickers scale (HV0.5) on polished surfaces at room temperature. According to XRD results, hot pressing process crystallite size increase and microstrain decreases in the compact samples due to the release of crystalline defects. The compacted samples have porosity of approximately 20%. The milling powder samples have a higher hardness than the unmilled samples, this because during milling crystal defects are incorporated together with the microstructural refinement. Ternary alloy is the one with the highest hardness of all systems studied, reaching 689 HV0.5. In compression tests determined a strain 5 %, Zr-containing samples become more fragile presenting the lowest values of compressive strength. In contrast, samples of Ni and Cu-Ni binary alloy are more resistant to compression. Copyright © Materials Research Society 2017.